2009
DOI: 10.1016/j.ijgo.2009.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about HIV infection and acceptability of HIV testing among women delivered in Podkarpackie Province, Poland

Abstract: These pregnant women from Poland, where prenatal HIV testing is rarely done, showed a limited knowledge of perinatal HIV transmission but a high willingness to undergo HIV testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The searches yielded 15 004 records after de‐duplication; after full‐text review, 368 studies were included in the overall systematic review (Figure ). Of the 368 studies, 130 are described in this paper, exploring interventions and feasibility of HIV testing in health care settings in Europe, including 84 peer‐reviewed articles and 46 conference proceedings (Table ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The searches yielded 15 004 records after de‐duplication; after full‐text review, 368 studies were included in the overall systematic review (Figure ). Of the 368 studies, 130 are described in this paper, exploring interventions and feasibility of HIV testing in health care settings in Europe, including 84 peer‐reviewed articles and 46 conference proceedings (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were from Northern Europe ( n = 78; 64%), followed by Western ( n = 23) and Southern Europe ( n = 24). There was only one study from Eastern Europe and four studies set across multiple European countries . The majority of the studies from Northern Europe were from the UK (92%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dube and Nkosi [43] found that half of the women in their study felt 50% of respondents expressed willingness to be tested in a Chinese study by Li et al [36] and in an Ethiopian study by Moges and Amberbir [37] ; in contrast, other studies reported higher willingness to be tested (more than 75% of respondents expressed willingness to be tested) [38][39][40] . Some African studies demonstrated significant gaps between the willingness of pregnant women to receive HIV testing and their actual testing rates, as in studies from Sudan [41] and Tanzania [42] .…”
Section: Fear Of the Test Resultsmentioning
confidence: 94%
“…Most reviewed studies demonstrate that women's willingness to be tested for HIV during pregnancy was influenced by their knowledge about HIV/AIDS and MTCT [36,37,39,41,58,60,[72][73][74] . Other studies found that knowledge was not related to willingness to be tested.…”
Section: Knowledge Perceived Susceptibility To Hiv and Perceived Bementioning
confidence: 99%